Factors Influencing E-Loyalty in E-Commerce Platforms: A Case Study of Gen Z and Millennial Users on Tokopedia - Putra, Dimas Kurnia; Purba, Laura Fransisca; Manaf, Peri Akbar (Dinasti Publisher, 2025)
This study aims to analyze the factors influencing e-loyalty on Tokopedia by focusing on Gen Z and Millennial users in Jabodetabek. The research investigates e-service quality and perceived value as independent variables, e-satisfaction as a mediating variable, and e-loyalty as the dependent variable. Data were collected through an online survey of 280 respondents who had used Tokopedia between 2021 and 2024. Partial Least Squares-Structural Equation Modeling (PLS-SEM) was applied for analysis. The findings reveal that e-service quality and perceived value significantly affect e-satisfaction; e-service quality directly influences e-loyalty; and e-satisfaction mediates the relationship between both independent variables and e-loyalty. The results highlight the importance of digital service quality and perceived value in building satisfaction and loyalty, particularly among younger generations who are prone to switching platforms. These insights provide strategic implications for Tokopedia to strengthen customer retention in a highly competitive e-commerce landscape.